Experimental study on the performance of membrane based multi-effect dehumidifier regenerator powered by solar energy - Chakraborty, Anutosh (2014)
This study aims to provide an experimental performance analysis of a membrane based multi-effect regenerator for dehumidification application powered by solar thermal energy. The regenerator system is used as a desiccant solution concentrator to re-concentrate the salt solution by removing some water content in the used solution from the de - humidification system. The concentrated solution can also be used as a solar energy storage system by storing the high concentrated desiccant solution to be used in the de-humidifier. In the membrane based multi-effect regenerator, the merits of multi-effect evaporation and membrane's mass transfer process are applied. It uses an energy recovering process by using the multi-effect evaporation concept and the membrane's mass transfer process driven by low grade temperature and pressure gradient. In this study, different operating parameters such as feed flow rates, feed concentration and heating temperature were examined to determine the optimum performance of this membrane based multi -effect regenerator.